Iron Oxide and Graphene Oxide nanocomposite with Polymethyl Methacrylate as innovative Pour Point Depressant for Waxy Crude Oil of North-East India - Khaklari, Gaurav Himanta; Talukdar, Prasenjit (International Journal of Membrane Science and Technology, 2023)
This paper focuses on the transportation challenges associated with waxy crude oil found in the North-Eastern region of India, particularly in Assam. The high paraffin and wax content in the crude oil leads to issues such as high pour point and viscosity, which can obstruct the flow of oil and cause disruptions in the transportation process. In this study, a composite material consisting of Graphene Oxide (GO) and Iron Oxide (Fe3O4) was synthesized and evaluated in crude oil rheology test. This study includes the characterization of the waxy crude oil sample e.g., specific gravity, API gravity, pour point, water content, wax content, FTIR analysis and SARA distribution. The dispersion stability of the rGO-Fe3O4 composite material was tested in polar (water) and nonpolar (xylene) solvents. The composite material showed high hydrophobicity and remained insoluble in water, while it dissolved in xylene. The rheological test for the crude oil and Pour Point depressant (PPD) such as viscosity, shear stress, storage modulus, loss modulus etc., were also performed. The crude oil sample's pour point was effectively reduced by 18°C with the application of a 500-ppm dosage. The findings of this research contribute to a better understanding of the challenges associated with transporting waxy crude oil and offer insights into the potential use of nanocomposite PPDs (NPPD) for improving the flow properties of the oil.